Treatment-related pulmonary adverse events induced by chemoradiation and Durvalumab affect survival in locally advanced non-small cell lung cancer. (November 2022) - Xu, Ting; Wu, Lirong; Gandhi, Saumil; Jing, Wang; Nguyen, Quyhn-Nhu; Chen, Aileen; Chang, Joe Y.; Nurieva, Roza; Sheshadri, Ajay; Altan, Mehmet; Lee, Percy P.; Lin, Steven H.; et al.
Highlights: Adjuvant ICI increased symptomatic pulmonary adverse events. Adjuvant ICI improved survival and disease control. Pulmonary adverse events were the major cause of ICI discontinuation. Discontinuation of ICI led to poorer survival and distant disease control. Abstract: Purpose: We compared treatment-related pulmonary adverse events (TRPAE), progression-free survival (PFS), and overall survival (OS) among locally advanced non-small cell lung cancer (NSCLC) patients who received concurrent chemoradiotherapy (CRT) versus CRT followed by immune check point inhibitor (ICI) immunotherapy (CRTI). Materials and methods: TRPAE was defined as any pulmonary events as defined in CTCAE v.5 occurring within 12 months after completion of radiotherapy. Outcomes were compared between CRT and CTRI by Cox proportional hazard regression and Kaplan-Meier analyses. We also assessed if TRPAE-induced discontinuation of ICI affected survival. Results: We analyzed 326 patients treated between July 2010 and November 2019; 195 patients received CRT and 131 received CRTI. The incidences of severe grade ≥ 3 TRPAE were similar between the two groups, however, symptomatic TRPAE was almost doubled in CRTI group (65.7 % CTRI vs 35.9 % CRT, P  < 0.0001). The rates of 4-year OS and PFS were 54.5 % vs 36.7 % ( P  = 0.0003) and 43.8 % vs 35.8 % ( P  = 0.038) in CRT + Durvalumab and CRT group, respectively. Receipt of ICI Durvalumab was associated with better 4-year OS (HR 0.53, 95 % CI 0.36–0.78, P  = 0.001) and PFS (HR 0.55, 95 % CI 0.38–0.80, P  = 0.002). Patients who discontinued ICI because of TRPAE had worse 4-year OS ( P  = 0.001) and higher rates of distant metastasis ( P  = 0.003) than those who completed planned ICI after developing TRPAE. Conclusion: CRT followed by adjuvant ICI led to improved 4-year OS and PFS consistent with published data. CRTI was associated with higher incidence of grade ≥ 2 TRPAE in both high and low mean lung dose groups without significant difference in grade ≥ 3 TRPAE. Discontinuation of ICI due to TRPAE was associated with poorer OS and distant disease control than completing ICI as planned after developing TRPAE.